(untitled) (Journal of Student Affairs in Africa, 2023)
Student affairs practitioners and researchers are well positioned to contribute holistically to student success and as such could play a strategic role in the transformation of higher education. The aim of this article is to illustrate that a key strategic objective of student affairs is to contribute significantly towards student success. This article reports on a study (January, 2021) entitled ‘Towards a qualitative framework for blending equity and excellence in transforming South African higher education transformation to achieve development’ in which the promotion of student success is viewed as central to institutional transformation. The purpose of the study was to contribute to a more comprehensive qualitative framework for higher education transformation in South Africa by reconciling notions of ‘equity and excellence’. Interviews were conducted with sixteen leaders in the field of higher education in South Africa. Thereafter, interview data were triangulated with strategic documents of various entities concerned with higher education transformation. The theoretical framework encapsulated the human capital and human capability theories and argues further for a reconciliation of these theories to promote social justice and human well-being. The study used grounded theory methods to analyse and present the comprehensive qualitative framework. The study found that student success was the most critical factor driving institutional transformation. In addition, four other interrelated elements were presented as the core elements of a comprehensive framework. Based on these findings, this article explores the implications for student affairs further, using unpublished input gathered by the author through reflective conversations with stakeholders at the University of Cape Town. In this regard the notion of a set of student learning imperatives (graduate attributes) becomes relevant to the discussion when student affairs practitioners and researchers collaborate with faculties and departments on strategic projects.